The role of the school climate in high school students' mental health and identity formation: A South Australian study - Riekie, H.; Aldridge, Jill; Afari, E. (Carafax Publishing, Taylor & Francis Group, 2016)
The well-documented increase in student mental health issues in Australia and growing recognition of the need for education to play a part in students' identity formation prompted this study. The research reported in this article sought to identify specific elements of the school climate that were likely to influence the interplay of adolescent health and development and students' identity formation. The aim was two-fold. First, the study examined the relationships between students' perceptions of the school climate and self-reports of wellbeing, resilience and moral identity; and, second, the interrelationships between the three outcome variables were explored. Two surveys, one to assess students' perceptions of features of the school climate, and another to assess students' wellbeing, resilience and moral identity, were administered to 618 Year 11 students from 15 independent schools in South Australia. Structural equation modelling was used to investigate hypothesised relationships between students' perceptions of their school climate and self-reports of wellbeing, resilience and moral identity. Our results indicated statistically significant and positive relationships between school-climate factors and each of the three outcome variables. Further, indirect relationships (mediated largely by resilience) were found between school-climate factors and students' wellbeing. Our findings could be used to guide schools in building tangible, purposeful environments that engender well-balanced, positive, resilient citizens with strong moral identities.